A NEW ERA OF EARLY CHILDHOOD LEARNING - Ulum, Muhammad Samsul (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
The challenges faced by the world of education today are not light, due to technological revolution not only impacts social and cultural changes, but also on patterns of thought and behavior patterns. Responding to these challenges, Early Childhood Education seeks to improve the quality of education by conducting studies and evaluation of education at the level of Early Childhood. Any materials and methods to be delivered in Early Childhood Education should adhere to the following principles: 1. Maintain the nature, 2. Conducive environment, 3. Social interaction commensurate, 4. Guiding independence, 5. Simplicity (homeliness), 6. Balance (balance), 7. Sterilization from negative influence, 8. actual and factual experience.